Leukemia Inhibitory Factor (LIF) Overexpression Increases the Angiogenic Potential of Bone Marrow Mesenchymal Stem/Stromal Cells - Santos, Girlaine Café; Silva, Daniela Nascimento; Fortuna, Vitor; Silveira, Brysa Mariana; Orge, Iasmim Diniz; de Santana, Thaís Alves; Sampaio, Gabriela Louise; Paredes, Bruno Diaz; Ribeiro-dos-Santos, Ricardo; Soares, Milena Botelho Pereira (Frontiers in Cell and Developmental Biology, 2020)
Mesenchymal stem/stromal cells (MSCs) have the ability to secrete bioactive molecules, exerting multiple biological effects, such as tissue regeneration, reduction of inflammation and neovascularization. The therapeutic potential of MSCs can be increased by genetic modification to overexpress cytokines and growth factors. Here we produced mouse MSCs overexpressing human leukemia inhibitory factor (LIF) to assess their pro-angiogenic potential in vitro and in vivo. Mouse bone marrow-derived MSCs were transduced by using a second-generation lentiviral system to express human LIF. LIF expression was confirmed by qRT-PCR and by ELISA, allowing the quantification of the transcript and secreted protein, respectively. Flow cytometry analysis and trilineage differentiation assay showed that the MSC_LIF cell line maintained the immunophenotype and a multipotency characteristic of MSCs. The immunosuppressive activity of MSC_LIF was confirmed using a lymphoproliferation assay. Moreover, gene expression analysis demonstrated upregulation of genes coding for strategic factors in the neovascularization process, such as angiogenin, IL-8, MCP-1 and VEGF, and for the perivascular cell markers ɑSMA, Col4a1, Sm22 and Ng2. To evaluate the pro-angiogenic potential of MSC_LIF, we first tested its effects on endothelial cells obtained from umbilical vein (HUVECs) in a scratch wound healing assay. Conditioned medium (CM) from MSC_LIF promoted a significant increase in cell migration compared to CM from control MSC. Additionally, in vitro tube formation of endothelial cells was increased by the presence of MSC_LIF, as shown in microvessel sprouting in aortic ring cultures. Finally, an in vivo Matrigel plug assay was performed, showing that MSC_LIF were more potent in promoting in vivo angiogenesis and tissue vascularization than control MSCs. In conclusion, LIF overexpression is a promising strategy to increase the proangiogenic potential of MSCs and sets precedents for future investigations of their potential applications for the treatment of ischemic diseases and tissue repair.